PENGARUH BELANJA MODAL TERHADAP INDEKS PEMBANGUNAN MANUSIA DENGAN PENDAPATAN ASLI DAERAH SEBAGAI VARIABEL MEDIASI: STUDI PADA KOTA/KABUPATEN DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA PERIODE 2014-2024 - Rahman, Abiyan; Priyastiwi, Priyastiwi (Universitas Sarjanawiyata Tamansiswa, 2025)
The Human Development Index (HDI) is a key indicator used to measure the quality of development in a region. However, improvements in HDI do not always align with the amount of capital expenditure allocated by local governments. This raises questions about the effectiveness of capital expenditure in promoting human development, as well as the potential influence of other contributing factors. This study analyzes the direct and indirect effects of Capital Expenditure on the Human Development Index (HDI), with Local Own Revenue (PAD) as a mediating variable. Using panel data from cities/regencies in Yogyakarta Special Region (DIY) for the period 2014–2024, the analysis employs path analysis with multiple linear regression and the Sobel test. The results show: (1) Capital Expenditure has a positive and significant effect on PAD; (2) PAD has a positive and significant effect on HDI; (3) the direct effect of Capital Expenditure on HDI is positive but not statistically significant; and (4) Capital Expenditure has a significant indirect effect on HDI through PAD, confirmed by the Sobel test (z = 3.46; p < 0.05). The main conclusion is that PAD serves as a full mediator in the relationship between Capital Expenditure and HDI, indicating that the effectiveness of Capital Expenditure in improving HDI works through enhancing local fiscal capacity.